Histochemical studies on the cervix of buffalo (Bubalus bubalis) during post natal development - UPPAL, VARINDER; ROY, K S (The Indian Journal of Animal Sciences, 2013)
Histochemical studies were conducted on the cervix of 24 Indian buffaloes of 4 age groups of 6 animals each viz. neonatal, prepubertal, cyclic and pregnant. The study rev ed that among various groups the distribution of neutral mucopolysaccharides (NMPS), acid mucopolysaccharides (AMPS), basic protein, glycogen and lipid was comparatively better localized in the cervix of neonates. This beUcr localization may be related with their growth and physiological requirement. However, increased NMPS during pregnancy may be due to increased concentration of mucoproteins in cervical mucosa required to fonn the mucous plug of pregnancy.